Head-tail linkage constructions in quichua santiagueño (ALPHA. Journal of Arts, Literature and Philosophy, 2021)
In many languages preposed adverbial clauses repeat the previous verb or predicate, which phenomenon has been termed tail-head linkage (THL henceforth, Thompson & Longacre, 1985; de Vries, 2005). This paper aims to describe THL constructions in Quichua Santiagueño (Quechua) according to two parameters: a) the degree of semantic overlap between the predicates of the THL constructions, and b) the degree of event integration of the preposed adverbial with its main clause. The first parameter allows the identification of verbatim constructions –with exact repetition of the previous predicate– and non verbatim constructions –without exact repetition–. The second parameter manifests itself in the form the head clause might adopt, where it is a converb or it takes switch reference suffixes. The interplay of both parameters shows that the different THL constructions possess diverse discourse functions, particularly regarding thematic coherence (Givón, 2001).
Keywords: Santiagueño Quichua; head-tail linkage; adverbial clauses; thematic coherence